Analisis Rasio Keuangan pada Emiten Pelayaran di Asia Tenggara - Said Kelana Asnawi (Universitas Bandar Lampung (UBL), 2010)
This study discusses the Financial Ratios of Listed shipping in Southeast Asia consisting of: 7 (seven) shipping issuers of Indonesia, 2 (two) issuers of Malaysia and one (1) Issuer of Singapore. Financial Ratio Analysis is an important thing that needs to be done against the shipping issuer. This study aims to provide a narrative description regarding the use of financial ratios that serve as Standard Analysis Tool on the shipping industry. Financial ratio analysis results can provide insight into the condition and financial situation faced by the issuer on the shipping industry and can be used as a benchmark (rule of thumb) to determine the condition and financial situation of the issuers shipping industry. This study uses Quantitative Analysis Method using the formula of Financial Ratios Liquidity Ratios, Solvency Ratios, Activity Ratios and Profitability Ratios. The discussion carried out simultaneously for all issuers to make comparisons to determine the condition of the industry and the financial situation of the Issuer. Based on the analysis results can be concluded that: issuer has a good Liquidity Ratio (CR> 1) but there were a range of variation of a high ratio between the issuer, which can not be used as a benchmark (rule of thumb). This shows that there are sharp differences between the issuer in terms of managing its financial management. Also obtained a standard (rule of thumb) that the Asset Turnover Ratio (ATO) is generally the amount ranges from less than 1 (one), but Receivable Turnover Ratio (Arto) and Ratio Inventory Turnover (ITO) has a high variation. Indonesia issuer has Return on Assets (ROA) <6%, but the Return on Equity (ROE) and Profit Margin (PM) have a high variation. The ratio of EBITDA / Assets is found positive for the Indonesia issuer.Penelitian ini membahas Rasio Keuangan dari Emiten Pelayaran di kawasan Asia Tenggara yang terdiri dari: 7 (tujuh) Emiten Pelayaran dari Indonesia, 2 (dua) Emiten dari Malaysia dan 1 (satu) Emiten dari Singapura. Analisis Rasio Keuangan merupakan hal penting yang perlu dilakukan terhadap Emiten Pelayaran. Penelitian ini bertujuan untuk memberikan uraian deskriptif berkenaan dengan penggunaan Rasio Keuangan yang berfungsi sebagai Alat Analisis Jurnal Manajemen dan Bisnis Vol. 1 No. 1 Oktober 2010 : 33-49 34 Standar pada Industri Pelayaran. Hasil analisis Rasio Keuangan dapat memberikan pemahaman tentang kondisi dan situasi keuangan yang dihadapi oleh Emiten pada Industri Pelayaran dan sekaligus dapat digunakan sebagai patokan (rule of thumb) untuk mengetahui kondisi dan situasi keuangan pada Emiten Industri Pelayaran. Penelitian ini menggunakan Metode Analisis Kuantitatif dengan menggunakan Rumus Rasio Keuangan yang terdiri dari Rasio Likuiditas, Rasio Solvabilitas, Rasio Aktivitas dan Rasio Profitabilitas. Pembahasan dilakukan secara bersamaan untuk semua Emiten dengan melakukan perbandingan untuk mengetahui kondisi industri dan situasi keuangan dari Emiten. Berdasarkan hasil analisis dapat disimpulkan bahwa: Emiten memiliki Rasio Likuiditas yang bagus (CR>1) namun terjadi rentang variasi rasio yang tinggi antar Emiten, sehingga tidak dapat dijadikan patokan (rule of thumb). Hal ini menunjukkan adanya perbedaan yang tajam antar Emiten dalam hal pengelolaan menejemen keuangannya. Selain itu diperoleh patokan (rule of thumb) bahwa Rasio Perputaran Asset (ATO) secara umum besarnya berkisar kurang dari 1 (satu ), namun Rasio Perputaran Piutang (ARTO) dan Rasio Perputaran Inventori (ITO) memiliki variasi yang tinggi. Emiten Indonesia memiliki Imbal Hasil Asset (ROA) < 6%, namun Imbal Hasil Modal Sendiri (ROE) dan Marjin Laba (PM) memiliki variasi yang tinggi. Rasio EBITDA/Asset ditemukan bernilai positif untuk Emiten Indonesia.